Spectrophotometric Determination of Losartan Potassium and Hydrochlorothiazide in tablets by Wavelet Transform Approach - Özgür Üstündağ; Erdal Dinç (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
A precise, rapid and simple spectrophotometric method development with continuous wavelet transform technique was described in this paper for the simultaneous determination of losartan potassium and hydrochlorothiazide in tablets. The continuous wavelet transform approach based on the application of Symlets5-CWT. If the original UV spectra of losartan potassium and hydrochlorothiazide are examined, it is seen that the spectra of these two substances strongly overlap. With the developed Symlets5-CWT method, the analysis was carried out successfully without any pre-separation process. The calibration equations were obtained at 247.7 nm for the losartan potassium determination and at 259.1 nm for the hydrochlorothiazide determination, respectively. The developed methods were tested in terms of validity and applicability.